Fa’āliyatu Tadris Al-Lugah Al-‘Arabiyah Fi Al-Kitāb “Modul Hikmah” Fi Al-Shaffi Al-‘Asyiri Li Al-Madrasah Al-Tsanawiyyah Al-Islamiyyah Al-Hukumiyyah Pakem Sleman Bi Yogyakarta - Mohd. Fikri Azhari (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2020)
This study aims to determine the method of teaching Arabic by using the book "Wisdom Module" in the success of reading skills at MAN Pakem Sleman Yogyakarta and to find out the extent of the effectiveness of Arabic teaching by using the book "Module Wisdom" in the success of reading skills at MAN Pakem Sleman Yogyakarta. The results of this study are expected to be a scientific paper that is able to enrich insights about learning Arabic, especially insights for teachers to choose the right method, especially adjusting the ability of students in learning. This type of research is Field Research (field research) by taking a location in MAN Pakem Sleman Yogyakarta. Data collection is done by using methods of observation, interviews, documentation, questionnaires. Data analysis techniques are performed using non-statistical data analysis or descriptive data analysis. The results showed that: 1 method used by teachers in teaching Arabic is the method of memorization, reading, examinations, and question and answer. And the Al-Qiroah Method used by the teacher is divided into two, 1. Silent reading, 2. Hard reading. 2. The effectiveness of teaching Arabic by using the book "Wisdom Module" has been effective, and get high results and Arabic exam results (excellent reading) "very good". Can be proven the results of class 10, namely: 83.82 and this is in accordance with Suharsimi Arikunto in his book that is 80-100 and very good interview with Ustad Muhammad Rosid that students are already interested in reading Arabic texts in the book "Wisdom Module" and this very good, and he also said that the use of the book "Wisdom Module" is very effective than the use of books from school. التجريد يهدف البحث لمعرفة طريقة تدريس اللغة العربية فى الكتاب "مودل حكمة" فى نجاح مهارة القراءة للمدرسة ا الثانوية الإسلامية الحكومية فاكم سليمان بيوكياكرتا. لمعرفة فعالية التدريس اللغة العربية فى الكتاب "مودل حكمة" فى نجاح مهارة القراءة للمدرسة الثانوية الإسلامية الحكومية فاكم سليمان بيوكياكرتا. والمرجو من نتائج هذا البحث أن يكون بحثا عمليا يزيد علي معرفة فى تعليم اللغة العربية و خصوصا فى اختيار المناهج المناسبة و الموافقة بمهارة الطلاب فى اللغة العربية. هذا البحث بحث ميداني فى المدرسة الثانوية الإسلامية الحكومية فاكم سليمان بيوكياكرتا. وطرق جمع البيانات هي طريقة المراقبة, والمقابلة, وطريقة الوثائق و الإستفتاء. وطريقة تحليل البيانات بطريقة تحليل البيانات غير إحصائية أو الوصفي. دلت نتيجة هذا البحث : 1. أن طريقة التى استخدمه المعلّم يعنى طريقة الحفظ, وطريقة القراءة,و طريقة الإختبار, وطريقة التساؤلات. وتنقسم طريقة القراءة التى استحدمه المعلّم إلى قسمين: 1(. القراءة الصامتة , 2. القراءة الجهرية). 2. فعالية تدريس اللغة العربية فى الكتاب "مودول الحكمة" فعّال, وتؤدى إلى نتيجة عالية وحصول الإختبار اللغة العربية "جيد جدا" ودليل علي أن نتيجة من الصف العاشر 84,82 وهذا مناسب مع سوحارسم أريكونتو فى كتبه يعنى 80-100 "جيد جدا".والمقابلة مع الأستاذ محمد رشيد أن أكثر الطلاب قد مهرو فى قراءة النصوص اللغة العربية فى الكتاب "مودول الحكمة", وهذا أحسن. وقال أيضا أن استخدام الكتاب "مودول الحكمة" أشد فعلا من استخدام كتاب اللغة العربية من المدرسة. الكلمة الر ئيسية : فعالية تدريس اللغة العربية، الكتاب "مودول حكمة" , مهارة القراءة